Простори невизначеності та ізоморфізм - Diduk, N. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Some properties of uncertainty spaces (US) have been considered. A way of formalization by means of US for informal uncertainty situations (probability situations, nonstructural, fuzzy situations) has been shown. The notion of US isomorphism has been derived and applied for defining homogeneous US.